A Hard-to-Detect Signature Forgery Method “Freehand Simulation”: Case Report - Kırcı, Güven Seçkin; Aydoğdu, Halil İlhan; Okumuş, Hasan; Özer, Erdal; Eryılmaz, Ahmet; Birincioğlu, İsmail (The Bulletin of Legal Medicine, 2017)
Background: Signature is defined as any kind of distinctive mark which assures the identity of its generator in a certain way while demonstrating the generator’s will for approval of the content of the document to which it is subscribed, not limited to those generated with a person’s handwriting, Forged signatures, that is, the signatures not generated by its owner himself on the related document, can be produced by various methods. Those methods can be listed as tracing, freehand simulation using a model, freehand simulation from memory, revenue stamp transferring, photocopying or computer assisted reproduction techniques and fabricating on behalf of imaginary identities. Generation via signature machines, a recently invented way gradually becoming more frequent, can be added to this list. Freehand simulation from memory is distinguished from other afore-mentioned methods in certain aspects. Simulator studies the genuine signature carefully for days, learns its all features by heart, make trials of generation and finally executes the simulation in one move when convinced for success. This method is the hardest to reveal for examiners with its distinct features.Case: In our case, the signature subject to forgery investigation and the signatures obtained for comparison were found to be similar in signature characteristics such as signature velocity, dysfluency (jerk), slant and pen pressure. With a more detailed examination, it is understood that signatures are far different regarding start and stop points, stroke settings and counts, upstroke and down stroke patterns. Considering those findings, it is inferred that signature subject to investigation is generated by simulation using freehand method by memory.Conclusions: In this study, a forgery case relatively hard to detect is presented with sample images with the aim to emphasize acting in a very sensitive manner and asking for experienced specialist view for such cases is a must.
Keywords: freehand simulation; signature forgery; questioned document